The affective foundations of high‐reliability organizing. (8th February 2014) - Vogus, Timothy J.; Rothman, Naomi B.; Sutcliffe, Kathleen M.; Weick, Karl E.
Summary The factors that compel individuals to exert the extraordinary effort needed to create high reliability—consistent error‐free performance under trying conditions—remain unspecified. Here, we propose that when individuals experience emotional ambivalence and prosocial motivation, it induces the broad thinking and other‐orientation that undergird mindful organizing and high reliability. Copyright © 2014 John Wiley & Sons, Ltd.